Temporal variations of PM2.5-bound platinum group elements in outdoor and indoor environments close to areas with traffic congestion. (1st February 2021) - Fang, Shengqiong; Zhao, Chenyu; Hu, Jian; Xing, Yanfeng; Meng, Qingqing; Yu, Xiaoyu; Wang, Hao; Wang, Pengjie; Zhang, Rui; Gao, Peng
Abstract: Every city in the world faces pollution problems caused by traffic congestion almost every day. Platinum group elements (PGE) have been accumulating in the urban environment as catalytic converters for automobile exhaust emissions control. This study aims to determine the temporal variations of airborne particulate matter (PM)-bound PGE [Platinum (Pt), palladium (Pd) and rhodium (Rh)] in areas close to traffic congestion hotspots. Compared with the morning peak time, the concentrations of Pt, Pd, and Rh in outdoor airborne PM samples (PM2.5 ) collected in winter during the evening peak time increased by 35.03%, 37.45% and 75.47%, respectively, and the corresponding indoor environment was 9.33%, 6.93% and 71.36%, respectively. Significant temporal variations of PM2.5 -bound Pt, Pd, and Rh concentrations were observed during the time period of the Spring Festival. From before to during the Spring Festival, the outdoor environment Pt, Pd, and Rh concentrations sharply decreased by 172.1%, 14.72% and 22.96%, respectively, while the indoor environment decreased by 228.0%, 300.6% and 129.5%, respectively. From a seasonal perspective, among PM2.5 collected from the outdoor environment, PGE concentrations are the highest in winter and the lowest in summer. The temporal variation of the ratios (Pt/Pd, Pt/Rh, and Pd/Rh) indicates that PM2.5 -bound Pd concentration increased in the vicinity of traffic congestion. Further, the increased diesel-based trucks with Pt-dominant catalytic converters may contribute to PM2.5 -bound Pt detected in the autumn and winter of the alpine area (e.g. Harbin). Graphical abstract: Image 1 Highlights: Traffic congestion has a substantial impact on the distribution of PGE in PM2.5 . Palladium had the highest relative concentrations in PM2.5 . Materials transportation characteristics impact PGM ratio in PM2.5 .